2020
DOI: 10.1111/jasp.12701
|View full text |Cite
|
Sign up to set email alerts
|

Can the chronic exclusion‐resignation link be broken? An analysis of support groups within prisons

Abstract: Social exclusion, especially when prolonged over time––has a strong impact on the individuals’ health and wellbeing. According to the Temporal Need‐Threat Model (Williams, 2009), the experience of chronic social exclusion inescapably leads to a condition of resignation, characterized by feelings of alienation, depression, helplessness, and unworthiness. However, few empirical studies have tested this prediction and its potential moderating factors. In this research, we identified the prison as a prototypical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 73 publications
1
15
0
1
Order By: Relevance
“…The available literature highlights that the quantity and quality of face-to-face social connections could influence the psychological health of individuals exposed to persistent conditions of exclusion (Baumeister and Leary, 1995). For instance, a study in the prison setting showed that inmates attending in-person group meetings presented significantly better mental health than prisoners who did not join the group sessions (Aureli et al, 2020). Similarly, face-to-face interactions with native people protected immigrants' psychological health from the harm of social exclusion (Marinucci and Riva, 2020b).…”
Section: The Impact Of Social and Physical Isolation On Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The available literature highlights that the quantity and quality of face-to-face social connections could influence the psychological health of individuals exposed to persistent conditions of exclusion (Baumeister and Leary, 1995). For instance, a study in the prison setting showed that inmates attending in-person group meetings presented significantly better mental health than prisoners who did not join the group sessions (Aureli et al, 2020). Similarly, face-to-face interactions with native people protected immigrants' psychological health from the harm of social exclusion (Marinucci and Riva, 2020b).…”
Section: The Impact Of Social and Physical Isolation On Mental Healthmentioning
confidence: 99%
“…Beyond the advancement of the psychological impact of the COVID-19 lockdown, the exceptional nature of the COVID-19 pandemic made it possible to study an objective form of social isolation on a large scale, instead of limiting the research on certain marginalized social groups (e.g., Aureli et al, 2020).…”
Section: Conclusion and Practical Implicationsmentioning
confidence: 99%
“…In this stage, people begin to recover from the immediate response they experienced in the reflexive stage by engaging in responses aimed at fortifying their threatened needs. Finally, prolonged ostracism experience can lead to the resignation stage, characterized by feelings of alienation and depression (Aureli et al, 2020; Riva et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on dealing and coping with rejection mainly focuses on intrapersonal coping strategies such as enjoying comfort foods (Troisi & Gabriel, 2011) and watching favoured television programmes (Derrick et al., 2009), or psychological factors that can protect one against the negative impact of social rejection such as psychological flexibility (Waldeck et al., 2017). Some recent work points to the potential of interpersonal coping by showing that interpersonal connections can buffer against the resignation stage (e.g., Aureli et al., 2020; Marinucci & Riva, 2020). The current work contributes to this growing body of work on coping with rejection by suggesting that talking to others about a social rejection experience is akin to sharing certain negative emotions such as shame (Finkenauer & Rimé, 1998) or disclosing personally sensitive information such as information about a stigmatizing condition (e.g., Cantisano et al., 2013, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Social support (Teng & Chen, 2012) and social connections (Aureli et al., 2020; Marinucci & Riva, 2020) are potential remedies for the negative impact of social exclusion. One‐way targets can tap into these benefits is by sharing their hurt with others.…”
Section: Social Sharing Of Social Rejectionmentioning
confidence: 99%